[Op eds by B. Dawson re: cigarette taxes] - Dawson, Brennan M (Tufts Archival Research Center, 2007)
Copies of op eds sent out from Brennan Dawson to newspapers in the key tobacco states. Compares Congress' efforts to repeal taxes on boats, jewelry, and air craft to current ideas about a "monster" tobacco tax. Discusses potential job loss.